2019
DOI: 10.1016/j.ccell.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial NOTCH Signaling Rewires the Tumor Microenvironment of Colorectal Cancer to Drive Poor-Prognosis Subtypes and Metastasis

Abstract: SummaryThe metastatic process of colorectal cancer (CRC) is not fully understood and effective therapies are lacking. We show that activation of NOTCH1 signaling in the murine intestinal epithelium leads to highly penetrant metastasis (100% metastasis; with >80% liver metastases) in KrasG12D-driven serrated cancer. Transcriptional profiling reveals that epithelial NOTCH1 signaling creates a tumor microenvironment (TME) reminiscent of poorly prognostic human CRC subtypes (CMS4 and CRIS-B), and drives metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
336
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(348 citation statements)
references
References 98 publications
12
336
0
Order By: Relevance
“…Conversely, we report here that loss of Prox1 blunted WNT activity and increased the production of multiple profibrotic factors, including TGF-β1 and MMP14. Of note, Notch hyperactivation reduces PROX1 expression (61) and generates desmoplastic, invasive CMS4-like tumors with high TGF-β signaling (59), whereas PROX1 suppresses Notch signaling in colon cancer cells (62). Taken together, these observations suggest a model in which fluctuations of intratumoral Notch and WNT activity, if sufficient to switch off PROX1, will initiate a conversion toward a distinct tumor phenotype, in which cancer cells by suppressing the antitumor activity of CTLs.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Conversely, we report here that loss of Prox1 blunted WNT activity and increased the production of multiple profibrotic factors, including TGF-β1 and MMP14. Of note, Notch hyperactivation reduces PROX1 expression (61) and generates desmoplastic, invasive CMS4-like tumors with high TGF-β signaling (59), whereas PROX1 suppresses Notch signaling in colon cancer cells (62). Taken together, these observations suggest a model in which fluctuations of intratumoral Notch and WNT activity, if sufficient to switch off PROX1, will initiate a conversion toward a distinct tumor phenotype, in which cancer cells by suppressing the antitumor activity of CTLs.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, additional blockade of VEGFA and ANGPT2, a vessel-destabilizing ligand of TIE2 and a clinical evidence indicates that epithelium-rich tumors with high WNT signaling respond best to chemotherapy, whereas outcomes are worst for patients with desmoplastic CRC (7,10,11). Increased TGF-β signaling or Notch hyperactivation has been shown to promote desmoplasia in CRC models (14,47,59), indicating that multiple pathways contribute to stromal expansion in a subset of MSS CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that NOTCH2 and NOTCH3, but not NOTCH1 (data not shown), are expressed at the interface between the ameloblastoma epithelium and the underlying stroma, which is a location pivotal for the acquisition of an invasive phenotype [65]. The presence of Notch ligands such as JAG1, DLL1, and DLL4 in malignant epithelial cells adjacent to the NOTCH2 + NOTCH3 + interface suggests a possible involvement of Notch signaling in the establishment of ameloblastoma invasiveness and in the interaction of malignant epithelial cells with the underlying stroma [18,53,66]. We observed that NOTCH3, JAG1, DLL1, and DLL4 are also expressed within the ameloblastoma tumor mass.…”
Section: Discussionmentioning
confidence: 95%
“…TGFb is an abundant cytokine in the tumor microenvironment and modulation of TGFb receptor has been shown to impact colorectal cancer progression in animal models by altering tumor-stroma signaling (20,21). We sought to determine whether exposure to tumor microenvironmental signals were sufficient to prime TGFb-naïve organoids and induce WNT independence in vivo.…”
Section: The In Vivo Tumor Microenvironment Is Sufficient To Prime Cementioning
confidence: 99%